Cumulative mild head injuries in football (soccer) :|ba comparison of cognitive defict and post-concussive symptomology between University of Pretoria (Ama Tucks) football players and University of Limpopo volleyball controls in South Africa - Maite, Patricia (My University, 2014)
The aim of the study was to investigate the effect of Cumulative Mild Head Injury (CMHI) or concussion and Post-Concussive symptomatology of football players. For this purpose, a non-equivalent quasi experimental design of fifteen (15) professional football players and non-contact control group of fifteen (15) university volleyball players were assessed on 4 reaction time tasks and Post-Concussion Symptom questionnaire. The main findings of the study showed no significant difference on cognitive changes among football players and the control group. However, the two sample t-test, ANOVA and ANCOVA analysis in respect of both football players and the volleyball control group, provided significant results of a probability of CMHI or concussion on the CALCAP’s Sequential 1 Reaction Time Test. The study makes important theoretical and practical contributions to the understanding of Post-Concussion syndrome. The study suggests that some of the Post-Concussion symptoms persist after an initial concussion
Thesis (PhD (Psychology) ) -- University of Limpopo (Medunsa Campus) , 2010.
Keywords: Head injuries, glosed.; Head injuries.